The The Teacher’s EFL Practice in Implementing ELT Curriculum - Putri Meldia, Absharini Kardena (JADEs Journal of Academia in English Education, 2022)
This research is aimed at seeing how the English curriculum is implemented at Islamic Junior High School. This study employs a qualitative method: a case study. In collecting research data, observations, interviews, and document analysis become useful tools. This qualitative research used semi-structured interview questions and an observation checklist as the instruments, with an English teacher as the data source. One English teacher was involved in this study. In order to analyze the information gathered, the researchers used triangulated data. The information is then presented in a qualitative descriptive format. The findings show that while the concept of putting the 2013 curriculum into a document ; such as, syllabus and lesson plan has been well executed, teachers are having some difficulty putting it into practice in EFL classes. It could be indicated that the 2013 curriculum implementation in English subjects has been completed in written form, but the implementation in the teaching and learning process in the classroom has not been completed perfectly because the teacher is experiencing issues during the teaching and learning process and some of the challenges that an English teacher faces in implementing.